PENGARUH MICRO TEACHING DAN BIMBINGAN GURU PAMONG TERHADAP KEMAMPUAN MENGAJAR MAHASISWA MAGANG PROGRAM STUDI PENDIDIKAN EKONOMI STKIP PGRI TULUNGAGUNG - Sulastri Rini Rindrayani (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2016)
This research is a quantitative research that aims at knowing the effect of micro teaching and guidance from trainee teacher towards apprentice student’s teaching ability of Economics Departement of STKIP PGRI Tulungagung. Quesionare is used in data collecting method. The result of data analysis using multiple regression shows (1) There is significant positive effect between micro teaching and the apprentice student’s teaching ability, (2) There is significant positive effect between guidance of trainee teacher and the apprentice students’ teaching ability. (3) There is positive effect of micro teaching and guidance from trainee teacher towards the apprentice students’ teaching ability. The volue of effect is 44,2% , meanwhile 55,8% is influenced by other factors.